Poitiers - Musée Sainte-Croix - Statue d'Athéna - 1 - Benjamin Smith (Wikimedia Commons, 2025)
Notice iconographique issue de Wikimedia Commons. Titre: Poitiers - Musée Sainte-Croix - Statue d'Athéna - 1. Poitiers (Vienne, France) - Holy Cross Museum - Statue of Athena, 1st or 2nd c. AD
Licence Creative Commons Attribution-Share Alike 4.0 via Wikimedia Commons
Keywords: œuvre d'art; tableau; sculpture; statue; wikimedia commons